ACCESSING THE PERFORMANCE OF TELECOMMUNICATION INDUSTRY ON ECONOMIC GROWTH: EVIDENCE FROM MALAYSIA - KWANG HUI, HON (Universiti Malaysia Sarawak (UNIMAS), 2020)
Telecommunication industries have expanded rapidly in many countries over the past 20 years. The telecommunications technology development has been widely known as a driving force of globalisation and the world economy's rapid growth. Nowadays, the telecommunication sector continues to see substantial growth in Asia. This study accesses the telecommunication industry's performance on the economic growth in Malaysia by utilizing the quarterly time series data for a period from year 2010 to 2018. These data have been evaluated by employing various tests which are the unit root test, Johansen Juselius Cointegration test, VECM Granger causality and generalized variance decomposition. The empirical findings show that the telecommunication industry positively affects Malaysia's economic growth, while telecommunication investment shows insignificant effects on economic growth. The policymakers may relook the investment initiative in telecommunication. The future study may include more determinants of economic growth in the study.